TLR4 Links Podocytes with the Innate Immune System to Mediate Glomerular Injury - Banas, Miriam C. (American Society of Nephrology, 2008)
Toll-like receptors (TLR) classically recognize pathogen-associated danger signals but are also activated via endogenous ligands. For evaluation of their role in inflammatory kidney disease, the function of TLR was analyzed in two mouse models of cryoglobulinemic membranoproliferative glomerulonephritis (MPGN; mice transgenic for thymic stromal lymphopoietin [TSLP], with or without deletion of the Fcγ receptor IIb). Expression of TLR1 through 9 and TLR11 mRNA was detectable in whole kidneys and in isolated glomeruli of wild-type mice, with TLR3 and TLR4 having the highest absolute levels of expression. TLR1, 2, and 4 were increased in TSLP transgenic mice and even higher in TSLP transgenic FcγRIIb-deficient mice. TLR5 through 9 and 11 were upregulated to similar degrees in TSLP transgenic and TSLP transgenic FcγRIIb-deficient mice. Immunohistochemical studies of nephritic glomeruli localized TLR4 protein to podocytes. Cultured podocytes also expressed TLR4, and stimulation with TLR4-specific ligands resulted in a marked induction of chemokines; this was reduced by specific knockdown of TLR4 with siRNA. Fibrinogen, a potential endogenous TLR4 ligand, was shown to induce a similar profile of chemokines. In conclusion, it was demonstrated that TLR4 is constitutively expressed by podocytes and is upregulated in MPGN, where it may mediate glomerular injury by modulating expression of chemokines; therefore, TLR4 may link podocytes with the innate immune system to mediate MPGN triggered by the deposition of immune complexes.